Organizational Climate, Compensation, and DPRD Members’ Performance: The Mediating Role of Organizational Commitment - Jufri, Surya; Suhelmi2 , Suhelmi (International Journal of Digital Marketing Science, 2026)
This study aims to examine the effect of organizational climate and compensation on the performance of members of the Padang City DPRD, with organizational commitment as an intervening variable. A quantitative approach was employed using path analysis, with data processed through IBM SPSS version 25. The results indicate that organizational climate, compensation, and organizational commitment have positive and significant effects on members’ performance. A supportive organizational climate characterized by open communication, leadership support, and harmonious working relationships enhances legislative task effectiveness. Fair and proportional compensation, both financial and non-financial, directly improves performance and strengthens members’ loyalty. Furthermore, organizational commitment plays a mediating role that reinforces the influence of organizational climate and compensation on performance. These findings suggest that improving the performance of DPRD members can be achieved through the development of a positive organizational climate, transparent compensation systems, and sustained strengthening of organizational commitment.